Coming apart: The state of white America, 1960-2010 - Yu, QianQian (Journal of Interdisciplinary Studies in Education, 2017)
According to Murray, there have been socio-economic classes in America since its beginning. The main difference between the early 1960s and now is divergence on core behaviors and values among different socioeconomic classes in America. In the early 1960s, the civil rights movement was the biggest domestic issue. However, with the emergence of a new upper class and a new lower class, divergence has been increasing between the white new upper class and the white lower class in America. Sadly, the divergence continues to increase in our working, community, religious and educational environments.